Evaluation of Candida tropicalis (NCIM 3321) extracellular phytase having plant growth promoting potential and process development - Puppala, Kumar Raja; Naik, Tejali; Shaik, Alfina; Dastager, Syed; Kumar, V. Ravi; Khire, Jayant; Dharne, Mahesh (Biocatalysis and Agricultural Biotechnology, 2018)
Phytase is known to provide a solution for depletion of phosphorus (P). It helps it by hydrolyzing the insoluble P source in soil which is phytate. In this study, provides insight on yeast Candida tropicalis (NCIM 3321) which produces cell bound and extracellular thermostable phytase. The media components were optimized to enhance the enzyme production and checked for plant growth promoting activity. On optimization the isolate exhibited enhanced cell bound and extracellular phytase activity by four folds (from 236 to 1024 IU DCG⁻¹) and by five folds (from 0.46 to 1.95 IU ml⁻¹) respectively in 36 h. The production time decreased to 24 h compare to shake flask on Up-scaling the production process upto 10 L scale, thus increasing the productivity of cell bound (1810 IU DCG⁻¹day⁻¹) and extracellular phytase (6.08 IU ml⁻¹ day⁻¹). The crude phytase (12 IU) from NCIM 3321 strain was studied for plant growth promotion activity in lab scale and field level experiments with maize crop. Findings of the study revealed that the extracellular phytase derived from non pathogenic C. tropicalis (NCIM 3321) was found to be plant growth stimulating by increasing the available P in soil. Our findings of phytase isolated from non-pathogenic yeast C. tropicalis NCIM 3321 exhibited dephytinization potential. Therefore, current study may have profound application in sustainable agriculture.

Performance of Aspergillus niger (NCIM 563) phytase based feed supplement for broiler growth and phosphorus excretion - Puppala, Kumar Raja; Buddhiwant, Priyanka G.; Agawane, Sachin B.; Kadam, Avinash S.; Mote, Chandrashekhar S.; Lonkar, Vijaysinh D.; Khire, Jayant M.; Dharne, Mahesh S. (Biocatalysis and Agricultural Biotechnology, 2021)
Despite availability of commercial enzymes, the phytase produced from relatively inexpensive systems with high yields are gaining global attention in the feed industries in post-antibiotic era. We studied A. niger NCIM 563 Phytase produced in solid state fermentation (SSF) derived Koji powder and evaluated its utility in the poultry feed for broiler growth performance and phosphorous (P) excretion. The ability of phytase in the dried powder was estimated to dephytinize the poultry feed under simulated gastric conditions. Poultry feed was formulated using A. niger NCIM 563 phytase followed by a 42 days feed trial on broilers. After supplementation of phytase to the diet, there was a reduction of dietary P, maintained growth performance, skeletal development of broilers and reduced levels of phytic acid and available P in the litter. Extracellular phytase was able to replace up to 0.1% P in poultry feed. Minimal downstream processing a low-cost feed supplement with significant phytase activity could provide added advantage for anti-nutrition free poultry feed.
Keywords: Phosphorus; Phytase; Poultry feed; Solid state fermentation